Development of interactive video as learning media on fiber optic for class XI students of computer network engineering - Denada Anzalna; Rangga Firdaus; Bayu Saputra (Lighthouse Publishing, 2022)
This study aims to develop an interactive video on fiber optic material for students of class XI computer network engineering that is valid and practical. The subject of this research is class XI majoring in computer and network engineering at SMKN 4 Bandar Lampung. The method used in this research is R&D using the Branch development model which includes the ADDIE steps, namely the first; analysis (preparation and analysis of needs), second; design (designing the product to be developed), third; fourth development (Test material experts and media experts); product implementation (planning, preparation, testing educators' perceptions and student readability), fifth; evaluation. This development research produces products that meet the valid and practical categories.